A HISTORY CASE OF TOCILIZUMAB USAGE IN A PATIENT WITH SYSTEMIC JUVENILE IDIOPATHIC ARTHRITIS - R. V. Denisova; E. I. Alexeeva; T. V. Sleptsova ("Paediatrician" Publishers LLC, 2012)
The article represents a history case of successful usage of tolicizumab (anti-interleukin 6 monoclonal antibodies) in treatment of severe systemic juvenile idiopathic arthritis, resistant to previous standard antirheumatic therapy. Tocilizumab treatment led to distal joints function restoration and improvement of life quality in a short period of time. The drug prevented the continued progression of incapacitating injury and induced the clinical and laboratory remission of the disease.